2020
DOI: 10.1101/2020.07.11.20149344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Placental SARS-CoV-2 in a patient with mild COVID-19 disease

Abstract: Background: The full impact of COVID-19 on pregnancy remains uncharacterized. Current literature suggests minimal maternal, fetal, and neonatal morbidity and mortality,1 and COVID-19 manifestations appear similar between pregnant and non-pregnant women.2 We present a case of placental SARS-CoV-2 virus in a woman with an uncomplicated pregnancy and mild COVID-19 disease. Methods: A pregnant woman was evaluated at University of Missouri Women and Childrens Hospital. Institutional review board approval was o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
9
0
5
Order By: Relevance
“…Eighteen studies, involving 45 pregnancies, reported no evidence of pregnancy complications in their cases [ 16 , 22 , 23 , 26 , 27 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. There was no apparent increase in the frequency of maternal pregnancy complications in the remaining cases (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies, involving 45 pregnancies, reported no evidence of pregnancy complications in their cases [ 16 , 22 , 23 , 26 , 27 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. There was no apparent increase in the frequency of maternal pregnancy complications in the remaining cases (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia induced by maternal SARS-CoV-2 infection may lead to maternal vascular malperfusion (MVM) [ 54 ]; features or diagnoses of MVM were noted in 69 cases (46% of placentas examined, 95% confidence interval (CI) 38.1–53.9%) by 12 studies [ 25 , [28] , [29] , [30] , [31] , [32] , 34 , 43 , 44 , 51 , 52 , 55 ] ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Em estudo realizado com 10 recémnascidos de genitoras infectadas pelo vírus, seis apresentaram dificuldade respiratória, dois febre e um, taquicardia. Além disso, 4 desenvolveram sintomas gastrointestinais como sangramento gástrico, intolerância alimentar e inchaço, e 7 apresentaram alterações na radiografia torácica devido a infecções (Hsu et al, 2020).…”
Section: Discussionunclassified